Efficiency of levobupivacaine and bupivacaine for supraclavicular block: a randomized double-blind comparative study - Ilham,Cenk (2014)
Background and objectives: Success rate of catheter applications is low in supraclavicular block. Thus, bupivacaine and levobupivacaine become important with their long effect time in single injection practices. In this study, we aimed to compare the effectiveness, side effects and complications of bupivacaine and levobupivacaine in supraclavicular block. Methods: Sixty patients aged between 20 and 65, with body weight between 50 and 100 kg, in the ASA I-II-III group who were scheduled for hand, forearm and arm surgery using supraclavicular block were randomized into two groups of 30. The patients received 30 ml 0.5% bupivacaine (Group B) or 30 ml 0.5% levobupivacaine (Group L). Motor and sensory blocks were evaluated. Motor and sensory block onset times, total block durations, postoperative pain, amount of postoperative analgesic used and patient satisfaction were recorded. Results: Demographic data, distribution of surgical area and hemodynamic data were similar between the two groups. Surgery, motor and sensory block durations of Group B and L patients did not vary statistically significantly. However, motor and sensory block onset times in Group B were significantly shorter than Group L (p < 0.05). The mean time for first postoperative analgesic demand were 16.6 ± 8.0 h in Group B and 14.4 ± 7.3 h in Group L (p > 0.05). Conclusion: 30 ml 0.5% bupivacaine and levobupivacaine provide similar block characteristics for supraclavicular block. Bupivacaine leads to faster motor and sensory block onset compared to levobupivacaine however similar duration of postoperative analgesia.